Rekryteringsstrategier för företag inom skogssektorn : en undersökning om hur skogsbrukande och träförädlande företag bygger sitt arbetsgivarvarumärke - Toikkanen, Camilla (SLU/Dept. of Forest Products, 2003)
The forest industry is anonymous among the young people of today. Many youngsters do not know what the forest industry has to offer. As a result of this, many schools and forest have a weak recruitment. This is not a problem for Sweden and the forest industry only, many other businesses companies suffer from in Sweden and other countries in Europe share the same image problem.